(untitled) (Research, Society and Development, 2022)
COVID-19 affected more than 250 million of individuals and took more than 5 million lives globally, being declared as a pandemic. Due to person-to-person transmission, it is essential that healthcare workers wear Personal Protective Equipment to mitigate its dissemination. Despite its relevance, the prolonged usage of PPE leads to serious skin manifestations, decreasing its adherence. The aim of this study is to summarize the prevalence, type and the localization of skin lesions related to face masks, its risk factors, and preventive measures. An integrative review was conducted using MEDLINE, SCOPUS and EMBASE databases, through a search strategy involving descriptors and key terms, from the beginning of this research to January 25th, 2022. The literature research identified 4276 articles, and 37 met the eligible criteria and were included for analysis, representing 14897 participants. The prevalence rate of adverse effects was 42,23% (5409 out of 13119). The most common lesions found were itching, erythema and acne. The most damaged facial regions were nasal bridge, cheeks, chin and behind ears. The most common risk factors found were the use of N95 respirators, lengthy usage of masks and prior history of dermatitis. N95 respirators and similar ones were related to the highest rate of adverse effects and physiological parameters changes. The preventive measures had a positive effect amongst the studies. Therefore, the rate of injuries related to the usage of masks is high, and they should be faced as a public health issue so that interventions can be implemented.